On k-Cost Effective Domination Number in the Join of Graphs (European Journal of Pure and Applied Mathematics, 2021)
In this paper, we characterize the k-cost effective domination in the join of graphs.Further, we investigate the k-cost effective domination, cost effective domination index, maximal cost effective domination in the join of graphs.
Keywords: k-cost effective set; cost effective domination index; maximal cost effective domination.